The Role Of Public Relations In Crisis Management With Relevant Parties Sports Foundation -field Study Club Ess- - sahar, oumrtem (sports creativity, 2025)
:This study aims to know the awareness of the Algerian sports institutions and clubs about the importance and role of public relations in crisis management with parties related to the sports institution, And to maintain a positive image in the minds of the masses, and to achieve that we conducted a field study on the club ES Setif, through an interview with the charge of communication and public relations in the club. The results on the role of public relations in the management of crises within the Algerian sports institutions have reached the conclusion that the public relations of ES Setif have not reached the extent to which we can say that they operate at an effective pace, Allowing them to contribute to the general objectives of the institution, especially with regard to friction and interaction and good relations that create a good image among the masses both internal and external, allowing the adaptation and harmony of the institution with its sports environment and create a kind of confidence, , Which allows to win the respect of fans and the parties involved in the institution of sports, although the public relations department of the club plays an important role in the management of the crises facing the club, In various stages before and during the crisis, in order to maintain a good mental image about the club in the minds of the parties involved.